The Distributional Effects of Fiscal Consolidation - Ball, Laurence (IMF Working Papers; Working Paper ;, 2013)
This paper examines the distributional effects of fiscal consolidation. Using episodes of fiscal consolidation for a sample of 17 OECD countries over the period 1978-2009, we find that fiscal consolidation has typically had significant distributional effects by raising inequality, decreasing wage income shares and increasing long-term unemployment. The evidence also suggests that spending-based adjustments have had, on average, larger distributional effects than tax-based adjustments.